Prickly Pear Cactus Control in Pastures - Jason A. Ferrell; Brent A. Sellers (EDIS)
Prickly pear cactus is not a problem in every pasture in Florida, but where it is found, it is often the biggest and most difficult issue to manage: mowing prickly pear fragments the pads and dramatically increases the infestation, and although prickly pear doesn’t form dense canopies and doesn’t outcompete desirable forage grasses, its impact on grazing can be just as severe because of its barbed quills. This 2-page fact sheet was written by J. A. Ferrell and B. A. Sellers, and published by the UF Department of Agronomy, September 2011.